Bacteriocinogenic Clo DF13 Minicells of Escherichia coli Synthesize a Protein That Accounts for Immunity to Bacteriocin Clo DF13: Action of the Immunity Protein In Vivo and In Vitro - Kool, A. J. (1975)
The Clo DF13 plasmid-specific immunity protein is able to prevent the inhibitory effect of cloacin DF13 on in vitro protein synthesis. We have shown, by gel filtration, that direct binding of the Clo DF13 immunity protein to cloacin occurs in vitro. This cloacin DF13-immunity protein complex is rather stable, and the cloacin present in the complex is no longer able to cause inhibition of in vitro protein synthesis. The binding of immunity protein to cloacin DF13 is rather specific because the Clo DF13 immunity protein does not bind to in vitro inactive cloacin and binds very poorly to the closely related bacteriocin colicin E3. Furthermore, we present data which strongly suggest that in vitro at least a fourfold excess of immunity protein is required to ensure that every cloacin molecule is inactivated by cloacin-immunity protein complex formation. Only a fraction (an about equimolar amount) of the immunity protein molecules, however, actually binds to cloacin DF13. The existence of an immunity protein-cloacin complex in vivo was concluded from the observation that cloacin, purified by chromatography on diethyl-(2-hydroxypropyl)-aminoethyl Sephadex in the absence of urea, contains an about equimolar amount of a second protein which comigrates with immunity protein on sodium dodecyl sulfate-polyacrylamide and urea-polyacrylamide gels. In an in vitro protein-synthesizing system, this component appeared to behave identical to the Clo DF13 immunity protein. The purified immunity protein-containing cloacin was at least 80 times less active in inhibiting in vitro protein synthesis, compared to cloacin, free of immunity protein. These data imply that few, if any, cloacin DF13 molecules are present in cloacinogenic cells as active, free cloacin molecules.